Study on the status and influencing factors of elderly coronary heart disease patients in rural areas of Beijing (北京市农村老年冠心病患者自我管理现状及影响因素研究) - JIAO Meng (焦萌); YANG Dan (杨丹); MENG Jing (孟静) (Journal of International Translational Medicine Limited, 2023)
Objective To understand the current situation of self-management and its influencing factors of elderly coronary heart disease (CHD) patients in rural areas of Beijing. Methods Using the convenience sampling method, elderly CHD patients in rural areas of Beijing were selected, and their knowledge level, self-management attitude and self-management behavior were surveyed, and 221 valid questionnaires were collected. Results The knowledge level and self-management behavior of elderly CHD patients in rural areas of Beijing were at a low level, and their self-management attitude was at a middle level. The results of the multiple linear regression analysis showed that gender, education level, household per capita monthly income, primary support site of access to care, knowledge of CHD, and self-management attitude were entered into the regression model. Conclusion There is much room for improvement of the knowledge level, attitude and behavior of elderly patients in rural areas of Beijing. Patient gender, educational level, the per capita monthly family income, primary support site of access to care, the knowledge of CHD, and the self-management attitude are the factors influencing the self-management behavior of elderly CHD patients in rural areas of Beijing. (目的 了解北京市农村地区老年冠心病患者自我管理现状及其影响因素。方法 采用方便抽样法从北京市抽取农村老年冠心病患者, 对其知识水平、自我管理态度和自我管理行为进行问卷调查。共发放250份问卷, 回收有效问卷221份。结果 北京市农村老年冠心病患者关于冠心病知识水平、自我管理行为处于低水平, 自我管理态度处于中等水平。多元线性回归分析结果显示, 性别、文化程度、家庭人均月收入、获得护理主要支持地点、冠心病知识、自我管理态度进入回归模型。结论 北京市农村地区老年冠心病患者的知识水平、态度以及行为均有较大提升空间。患者的性别、文化程度、家庭人均月收入、获得护理主要支持地点、冠心病知识、自我管理态度是北京市农村老年冠心病患者自我管理行为的影响因素。)